Prospecção de técnicas para a fabricação de scaffolds biocerâmicos macroporosos para fins biomédicos - Oliveira, Tiê Menezes (2021)
The use of biomaterials in medicine has intensified as new treatments are emerging. Among biomaterials, an important segment that has attracted the attention of several scientists are bioceramics. These materials have various applications when it comes to bone tissue regeneration, generation and formation. Calcium phosphates, more specifically, hydroxyapatite, forms a large percentage of the composition of human bones and teeth. This compound is easily produced in laboratory with properties similar to those found in the human body naturally. The biomaterial is used mainly for the production of porous scaffolds in order to act as a bone graft and substitute techniques such as auto and allograft. This work validates the main manufacturing techniques of these scaffolds that are currently used, and studies the parameters of the porous ceramic structures production technique called direct foaming and tries to adapt the process for the production of hydroxyapatite scaffolds. Ceramic suspensions were produced with the aid of a mechanical stirrer and a sonicator in order to compare the dispersions produced, which had their rheological properties analyzed in a rotational rheometer. The scaffolds produced were observed by scanning electron microscopy for the study of the microstructure. Results indicate that, although the foaming technique is relatively simple, using few chemical reagents, working with ceramic materials involves several variables that need to be studied carefully só that scaffolds are produced with ideal parameters for application in medical research.